IDENTIFIKASI TINGGALAN JEPANG PADA MASA PERANG DUNIA II DI KELURAHAN MUNSE KECAMATAN WAWONII TIMUR KABUPATEN KONAWE KEPULAUAN - Eriani Eriani; abdul Rauf Sulaeman (SANGIA JOURNAL OF ARCHAEOLOGY RESEARCH, 2017)
his study it aims to determine the type of the remains of Japanese occupation in Wawonii and back to put the remains of the Japanese occupation. This Research using a theory of space and archeology battlefield. This research uses the technical method of data collection in the form of library research which collects literature related to the title of the study, the observation surface survey and data recording and interview. Then the stage of data processing and data analysis is using contextual analysis. The results of the study show that the remains found in the form of tubs, support structures, ground floor ,storage tanks, kitchen structures, Japanese caves, unidentified structures, used machinery, circular structures, floor structures and road structures. The factors behind the layout of buildings are political, security,environmental and economic factors . Political factors, namely the laying of remains in Munse can help wage thewar. The security factor is that the building's location is quite safe and strategic as a place to monitor navalenemy movements that enter through the Staring Baii doors. Environmental factors namely Japan utilizes hilly forest areas and terrain between mountains and hills which are somewhat closed but still can monitor enemy movements. Besides forest utilization, Japan also uses rivers and springs as sources of water. Economic factors,namely Japan uses naturalresources in agriculture for daily needs and Japanese war needs .